Functionalization of Mesoporous MCM‐41 (Nano)particles: Preparation Methodologies, Role on Catalytic Features, and Dispersion Within Polyethylene Nanocomposites. Issue 4 (26th November 2012) - Bento, A.; Lourenço, J. P.; Fernandes, A.; Cerrada, M. L.; Rosário Ribeiro, M.
Abstract MCM‐41 micro‐ and nanoparticles are prepared and functionalized with silane coupling agents. These pristine and silane‐decorated mesoporous MCM‐41s are further used in the synthesis of MCM‐41/ethylene nanocomposites by in situ polymerization, utilizing either supported or non‐supported catalytic systems. The catalytic behavior of those systems is discussed, taking into consideration the effects of the particle size, surface characteristics, and functionalization. The results have shown that the initial surface state of MCM‐41 is of paramount importance to achieve high catalytic activity if a polymerization catalyst is to be supported. Functionalization changes the surface chemistry, thus, a positive or negative effect may be observed, depending on the previous features of the surface. The particle size of MCM‐41 and its functionalization affect its final dispersion within the polymeric matrix, this distribution is evaluated by SEM, TEM, and microhardness measurements.